Unveiling the hidden clinical and economic impact of preanalytical errors - Lippi, Giuseppe (Türk biyokimya dergisi, 2025)
The preanalytical phase is the basis upon which the accuracy and reliability of laboratory testing mostly depend. Despite many recent advancements in laboratory medicine, preanalytical errors remain the most common source of diagnostic inaccuracies, accounting for up to 70 % of total laboratory mistakes. These errors can significantly impact patient outcomes, enhance healthcare costs, and impair laboratory efficiency. This article is hence aimed at exploring the various complexities of the preanalytical phase, examining the clinical and economic consequences associated with preanalytical errors, especially focusing on blood drawing and spurious hemolysis, which represent the most frequent causes of preanalytical problems in clinical laboratories.